Enhanced electrochemical performance of LiMnPO4 by Li+-conductive Li3VO4 surface coatings - Dong, Youzhong; Zhao, Yanming; Duan, He; Liang, Zhiyong (Electrochimica acta, 2014)
By a simple wet ball-milling method, Li3VO4-coated LiMnPO4 samples were prepared successfully for the first time. The thin Li3VO4 coating layer with a three-dimensional Li+-ion transport path and high mobility of Li+-ion strongly adhered to the LiMnPO4 material reduces Mn dissolution and increases the Li+ flux through the surface of the LiMnPO4 itself by preventing formation of phases on the surface that would normally block Li+ as well as Li+-ion permeation into the surface of the LiMnPO4 electrode and therefore improve the rate capability as well as the cycling stability of LiMnPO4 materials. The electrochemical testing shows that the 5% Li3VO4-coated LiMnPO4 sample shows a clear voltage plateau in the charge curves and a much higher reversible capacity at different discharge rates compared with the pristine LiMnPO4. EIS results also show that the surface charge transfer resistance and Warburg impedance of the Li3VO4-coated LiMnPO4 samples significantly decreased. The surface charge transfer resistance and Warburg impedance for the pristine LiMnPO4 are 955.1Ω and 400.3Ω, respectively. While, for the 5% Li3VO4-coated LiMnPO4, the value are only 400.2Ω and 283.6Ω, respectively. The surface charge transfer resistance decreases more than half. All of the improved performance will be favorable for application of the LiMnPO4 in high-power lithium ion batteries.